Essentials of circulating tumor cells for clinical research and practice - Liberko, Marian; Kolostova, Katarina; Bobek, Vladimir (Critical reviews in oncology/hematology, 2013)
The major cause of death due to cancer is its metastatic deposit in numerous tissues and organs. The metastatic process requires the migration of malignant cells from primary sites to distant environments. Even for tumors initially spreading through lymphatic vessels, hematogenous transport is the most common metastatic pathway. The detachment of cancer cells from a primary tumor into the blood stream is called epithelial-mesenchymal transition (EMT). As these cells circulate further in the bloodstream they are known as circulating tumor cells (CTCs). The CTC population is highly resilient, enabling the cells to colonize a foreign microenvironment. Alternatively, cancer stem cells (CSCs) may arise from differentiated cancer cells through EMT and an embryonic transdifferentiation process. The presence of CTCs/CSCs in blood seems to be a determining factor of metastasis. This paper reviews various methods of clinical cancer detection as well as the biology and molecular characterization of CTCs/CSCs. Our goal was to summarize clinical studies which used CTC/CSCs for prognosis in patients with breast, colorectal, prostate, lung, ovarian, and bladder cancer.
Keywords: Neoplasms; Neoplastic Stem Cells; Epithelial-Mesenchymal Transition; prognóza; Neoplastic Cells, Circulating; Cancer stem cells; Circulating tumor cells; Epithelial–mesenchymal transition; nádorové cirkulující buňky; Detection methods; Animals; lidé; Humans; zvířata; Clinical significance; Prognosis; nádory; nádorové kmenové buňky; epitelo-mezenchymální tranzice